Performance and cost comparison of extended length WDM-PON - Henning, Luiz Fernando; de Almeida Prado Pohl, Alexandre (2013 SBMO/IEEE MTT-S International Microwave & Optoelectronics Conference (IMOC), 2013)
Currently there is an effort by system operators to deploy cost effective Passive Optical Networks (PON). In this way, next generation PON is the subject of studies by researchers and system designers. Among them, Wavelength division multiplexing on Passive Optical Network (WDM-PON) are of particular interest once they can provide larger bandwidths. This work presents a comparison of WDM-PON configurations that employ a LED source, a directly modulated laser and a CW Laser with external modulation. Performance data and a cost comparison for the three cases are presented and discussed.